Constructing blame for school exclusion in an online comments forum: Membership categorisation analysis and endogenous category work. (December 2019) - Gibson, Will; Roca-Cuberes, Carles
Highlights: Membership Categorization provides an under-used and method for analysing news forums. Forum participants used textual resources indigenous to the forums to build arguments. Indigenous actions have been missed by researchers who have mostly used content analysis. Abstract: In this article we use Membership Categorisation Analysis to analyse conversations in an online forum in the British newspaper The Guardian. The comments thread followed an Op Ed piece that discussed the exclusion of 'under-performing' children in British secondary schools. Our analysis of these comments contributes to existing studies of online forums as a mode of public discourse and demonstrates the importance of research that focusses on interactional practices rather than on notions such as 'politeness' or 'framing'. We show the ways that participants used endogenous conversational categories to produce epistemic alignment and disalignment with each other, employing various strategies such as expanding category collections, creating relations between 'culpable' categories and 'trouble' categories, and re-describing categories through alternate category predicates. Through this, we see that the conversational actions undertaken in the forum are much more complicated than current concepts allow for, and we reflect on what such complexity might mean for the study and design of news forums.